2000
DOI: 10.1037/0893-164x.14.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Parenting practices as predictors of substance use, delinquency, and aggression among urban minority youth: Moderating effects of family structure and gender.

Abstract: This study examined how parenting factors were associated with adolescent problem behaviors among urban minority youth and to what extent these relationships were moderated by family structure and gender. Sixth-grade students (N = 228) reported how often they use alcohol, smoke cigarettes, or engage in aggressive or delinquent behaviors; a parent or guardian reported their monitoring and other parenting practices. Findings indicated that boys and those from singleparent families engaged in the highest rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
316
3
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(366 citation statements)
references
References 41 publications
28
316
3
12
Order By: Relevance
“…O apoio emocional proporcionado pelos pais também parece ser uma prática educativa que influencia mais as meninas, ou seja, as que nunca receberam apoio emocional dos pais foram consideradas como tendo alto risco para dependência de drogas no estudo. Além disso, esses autores afirmam que as meninas necessitam de um apoio maior da família como fator de proteção para dependência de drogas, enquanto os meninos necessitam de um apoio maior de seus pares, sugerindo que aparentemente as meninas respondem mais ao ambiente familiar 25 .…”
Section: Estilo Parentalunclassified
See 1 more Smart Citation
“…O apoio emocional proporcionado pelos pais também parece ser uma prática educativa que influencia mais as meninas, ou seja, as que nunca receberam apoio emocional dos pais foram consideradas como tendo alto risco para dependência de drogas no estudo. Além disso, esses autores afirmam que as meninas necessitam de um apoio maior da família como fator de proteção para dependência de drogas, enquanto os meninos necessitam de um apoio maior de seus pares, sugerindo que aparentemente as meninas respondem mais ao ambiente familiar 25 .…”
Section: Estilo Parentalunclassified
“…As mães tendem a monitorar de modo diferenciado meninas e meninos, monitorando mais as filhas que os filhos, o que as protege mais do abuso de drogas 2,25,29 .…”
Section: Estilo Parentalunclassified
“…Conversely, a high level of parental affection was associated with lower levels of substance use among Asian American adolescents (Guilamo-Ramos, Turrisi, Jaccard, Wood, & Gonzalez, 2004). Other research revealed that parenting monitoring served as a moderating factor between gender/family structure and substance use among minority adolescents (Griffin et al, 2000). When adolescents perceived less parental affection, they tended to more frequently interact with friends who used substances and engage in substance experimentation (Weiss & Garbanati, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Substance use (use of alcohol, tobacco, illicit drugs) among adolescents has been increasing in American society despite our best efforts at prevention (Fang, BarnesCeeney, Lee, & Tao, 2011;Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Ryabov, 2015;Shin, D'Antonio, Son, Kim, & Park, 2011;Wu, Woody, Yang, Pan, & Blazer, 2011). Those who use substances during their adolescence may experience irreversible negative outcomes because of their developing brains' vulnerability (Steinberg, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These parental practices predict adolescent positive outcomes (Griffin et al, 2000;Paschall, Ringwalt, & Flewelling, 2003;Smetana, Crean, & Daddis, 2002). According to Griffin et al (2000), more parental monitoring is associated with lower level of delinquency and served as a strong protective effect in boys than girls.…”
Section: Parent-child Relationship and Adolescents' Delinquencymentioning
confidence: 99%